Pendidikan Berkualitas Tanpa Diskriminasi: Studi Efektivitas Performance-Based Financing dalam Menutup Kesenjangan Mutu antara SD Negeri dan Swasta - Adriana, Adriana; Ayu, Dinda; Mulawarman, Widyamike Gede; Ayusaputri, Kusuma Galih; Haryaka, Usfandi (ALSYS, 2025)
Basic education is an important element in the development of the quality of human resources in Indonesia. However, the gap between public and private elementary schools (SD) is still the main obstacle in equitable access and quality of education. This difference is reflected in the variation in academic quality, educational facilities, and school management. One of the schemes introduced to address this problem is Performance-Based Financing (PBF), which provides funds based on school performance to improve the quality of education. This study aims to analyze the effectiveness of PBF in improving the quality of basic education and reducing the gap between public and private elementary schools. The main focus of the study is to evaluate the impact of PBF on students' academic quality, educational facilities, and school management. This study uses a quantitative approach with a quasi-experiment design, involving 40 elementary schools in the PBF intervention area, consisting of 20 public elementary schools and 20 private elementary schools. Data was collected through documentation of academic scores, observation of educational facilities, school management questionnaires, and interviews with principals. The results showed that the implementation of PBF increased students' academic scores (public elementary school: +5.8; private elementary schools: +5.5), the quality of educational facilities (improvement scores: +1.1 to +1.2), and the effectiveness of school management. Regression analysis showed a significant influence of PBF on education quality with R² 0.54 and p-value 0.001. The gap in quality between public and private elementary schools decreased from 2.6 points to 0.9 points. These findings suggest that PBF is effective in improving the quality of education, but requires additional policy support for more optimal outcomes.